2023
DOI: 10.3390/plants12051201
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic, Antioxidant, and Antimicrobial Activities of Bioactive Compounds from Avocado (Persea americana L.) Seeds

Abstract: The aim of this research was to identify and quantify biologically active compounds from avocado (Persea americana L.) seeds (AS) utilizing different techniques with the use of ultrasound (US), ethanol (EtOH), and supercritical carbon dioxide (scCO2) for possible applications in (bio)medicine, pharmaceutical, cosmetic, or other relevant industries. Initially, a study of the process efficiency (η) was carried out, which revealed yields in the range of 2.96–12.11 wt%. The sample obtained using scCO2 was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…The extracts of avocado seeds and mango peel did not present antimicrobial and antifungal activity. Other researchers point out that Hass avocado seed extract (Romaní et al, 2017), avocado seed (Kupnik et al, 2023), and mango peel (Lozoya-Castillo et al, 2018) inhibit the microbial growth of S. aureus and E. coli. This difference can be attributed to the extraction conditions.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts of avocado seeds and mango peel did not present antimicrobial and antifungal activity. Other researchers point out that Hass avocado seed extract (Romaní et al, 2017), avocado seed (Kupnik et al, 2023), and mango peel (Lozoya-Castillo et al, 2018) inhibit the microbial growth of S. aureus and E. coli. This difference can be attributed to the extraction conditions.…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
“…Antimicrobial and antifungal activity is assigned to phytochemical compounds such as polyphenols. The mechanism of action is due to the change in the function of cell membranes and the consequent slowing of growth and inhibition of microorganisms' reproduction (Singh et al, 2018;Kupnik et al, 2023). Moreover, seeds and agribusiness waste extracts also have many health-related bioactive properties, such as antihyperglycemic, anticancer, antihypercholesterolemic, antioxidant, anti-inflammatory, and antineurogenerative effects, which can be used to formulate or fortify foods (Kupnik et al, 2023;Sławińska and Olas, 2023;Sorrenti et al, 2023).…”
Section: Antimicrobial and Antifungal Activitiesmentioning
confidence: 99%
“…AS are rich in biologically active substances such as polyphenols, acetogenins, triterpenoids, and K. Kupnik et al: Bacterial Cellulose Membranes Enriched With Bioactive Compounds From Avocado Seeds 63 others (Jimenez et al 2021). In our recent study (Kupnik et al 2023), AS extracts exhibited significant antimicrobial activity against 13 out of 15 tested microorganisms, which often pose a problem in antimicrobial resistance, are transmitted by food or are colonized during food packaging. High concentrations of antimicrobial compounds, i.e., hesperidin, 2,3-dihydroxybenzoic acid, and vanillin, were found in AS extracts, which can synergistically contribute to high antimicrobial properties of AS extracts.…”
Section: Discussionmentioning
confidence: 75%
“…Previous research has demonstrated the rich phenolic content of avocado peel, highlighting its potent antioxidant and antimicrobial properties against foodborne pathogens (Kupnik et al, 2023;Sadiye, 2021). However, integrating avocado extract into composite coatings for extending the shelf life of perishable foods remains a relatively unexplored avenue.…”
Section: Introductionmentioning
confidence: 99%